MicroRNA expression in human omental and subcutaneous adipose tissue. - Nora Klöting (Public Library of Science (PLoS), 2009)
MicroRNAs (miRNAs) are small non-coding RNAs, that play important regulatory roles in a variety of biological processes, including development, differentiation, apoptosis, and metabolism. In mammals, miRNAs have been shown to modulate adipocyte differentiation. Therefore, we performed a global miRNA gene expression assay in different fat depots of overweight and obese individuals to investigate whether miRNA expression in human adipose tissue is fat-depot specific and associated with parameters of obesity and glucose metabolism. Paired samples of abdominal subcutaneous (SC) and intraabdominal omental adipose tissue were obtained from fifteen individuals with either normal glucose tolerance (NGT, n = 9) or newly diagnosed type 2 diabetes (T2D, n = 6). Expression of 155 miRNAs was carried out using the TaqMan(R)MicroRNA Assays Human Panel Early Access Kit (Applied Biosystems, Darmstadt, Germany). We identified expression of 106 (68%) miRNAs in human omental and SC adipose tissue. There was no miRNA exclusively expressed in either fat depot, suggesting common developmental origin of both fat depots. Sixteen miRNAs (4 in NGT, 12 in T2D group) showed a significant fat depot specific expression pattern. We identified significant correlations between the expression of miRNA-17-5p, -132, -99a, -134, 181a, -145, -197 and both adipose tissue morphology and key metabolic parameters, including visceral fat area, HbA(1c), fasting plasma glucose, and circulating leptin, adiponectin, interleukin-6. In conclusion, microRNA expression differences may contribute to intrinsic differences between omental and subcutaneous adipose tissue. In addition, human adipose tissue miRNA expression correlates with adipocyte phenotype, parameters of obesity and glucose metabolism.